Analysis on Cost-effectiveness and Budget Impact of Health Technology Assessment in Critical Care Medicine from the Global Health Perspective - Xuan Wang (International Journal of Public Health and Medical Research, 2026)
Critical care medicine is relatively expensive in terms of medical resources. Cost-effectiveness analysis (CEA) and its subset, cost-utility analysis (CUA), are employed in health technology assessment (HTA) to determine the economic value of intervention measures, and a separate budget impact analysis is performed to assess how the introduction of new technology will affect the budget. Both are used to make selections. This paper reviews the progress of health technology assessment (HTA) in the field of global critical care medicine, analyzes the application features of cost-effectiveness analysis (CEA) in the evaluation of ICU intervention measures, explores the methodological logic and practical value of budget impact analysis for technology access, and puts forward optimisation paths based on the actual constraints of middle-and low-income countries. A total of 219 full economic evaluation studies on ICU intervention measures have been published from 1993 to 2023. The number of publications has risen substantially in the past decade; only 1% originate from middle-and low-income countries, and 58% are model-based studies. In addition, there are many problems in the previous studies that make it difficult to draw broad conclusions. The World's critical care medicine HTA system should take both cost-effectiveness and budget impact into account and build a more flexible evaluation system for countries with different levels of resources.